Legal Responsibilities for Notaries Who Draw Nominee Agreement Deeds Relating to Ownership of Land Rights by Foreign Citizens in Bali - Kamalrullah, Rayhan Zhafrandy (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The objective of this research is to identify the various forms of notary liability for deeds that indicate legal smuggling due to their contradiction with the prevailing laws and regulations in Indonesia. The research method used is a normative juridical method with statutory, case, and analytical approaches. As we know, Indonesia’s agrarian law, as stipulated in the Basic Agrarian Law (UUPA), adheres to the principles of nationality and national sovereignty. This principle is enshrined in Article 9 paragraph (1) of the UUPA, which states that only Indonesian citizens may have a full legal relationship with land, water, and space, within the boundaries specified by law. However, to circumvent this regulation, parties often engage in land sale and purchase agreements using a nominee agreement or name-lending arrangement. Such actions may be classified as legal smuggling in the agrarian sector. A notary who participates in such legal smuggling by drafting deeds containing nominee agreements can also be held liable for the consequences of their actions.